2003
DOI: 10.1902/jop.2003.74.12.1785
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Distance from the Crest of Bone to the Height of the Interproximal Papilla Between Adjacent Implants

Abstract: Clinicians should proceed with great caution when placing two implants adjacent to each other in the esthetic zone. In most cases, only 2, 3, or 4 mm of soft tissue height (average 3.4 mm) can be expected to form over the interimplant crest of bone. These results showed that modification of treatment plans may be necessary when esthetics are critical for success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
231
2
25

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(269 citation statements)
references
References 4 publications
11
231
2
25
Order By: Relevance
“…2001, Tarnow et al. 2003) and eventually for the success of the implant‐supported prosthetic rehabilitation.…”
mentioning
confidence: 99%
“…2001, Tarnow et al. 2003) and eventually for the success of the implant‐supported prosthetic rehabilitation.…”
mentioning
confidence: 99%
“…20,21 Tarnow and his colleagues have shown the importance in maintaining the marginal bone height, as the response of the soft tissue height adjacent to the implant depended on the position of the bone level and the surrounding environment. 22 Tarnow et al has shown the clinical conditions and limitations, where a maximum retention of marginal bone and the soft tissue have been described. 22,23 Not all clinical situations allow to follow all the criteria to meet the satisfying aesthetic result from implant dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…We must remember that the soft tissue can fill a maximum of 5 mm vertically between two natural teeth, measuring the distance from the bone crest to the base of the contact point (25) . Nevertheless, average clinical measurements of soft tissue height between two implants were 3.4 mm (26) . Another negative aspect to consider is the loss of height of the interdental bone crest after the two adjacent teeth have been removed.…”
Section: Figmentioning
confidence: 93%
“…Debemos tener presente que el tejido blando es capaz de rellenar un máximo de 5mm en sentido vertical entre dos dientes naturales, tomando la distancia desde la cresta ósea hasta la base del punto de contacto (25) . Sin embargo, las mediciones clínicas de la altura del tejido blando entre dos implantes, dan un promedio de 3,4mm (26) . A esto se debe agregar como elemento negativo, la pérdida de altura de la cresta ósea interdental luego de la extracción de dos dientes vecinos.…”
unclassified